Designing geotechnical structures with a proper stability criterion as a safety factor. (January 2016) - Prunier, Florent; Chomette, Baptiste; Brun, Michaël; Darve, Félix
Abstract: Many geotechnical structures are built on sandy soils. This complex medium exhibits a non-associated rate-independent behaviour. Owing to this pattern, local and global tangent operators become non-symmetric. Consequently, it has been proved that instabilities and failure may develop before reaching the classic failure limit given by a plasticity limit. A proper analysis with the second-order work criterion allows for a good description of these instabilities and can be used as a good failure criterion. In this paper, we review the main results obtained in the last few decades when this criterion was applied to homogeneous problems. Then, a numerical integration of this quantity and a method for its normalization are proposed. The results of this integration lead to the definition of a safety factor for a global structure even under non-homogeneous conditions. Finally, an application to the design of a nailed wall is proposed. In this framework, a constitutive model that gathers the main basic features of soil behaviour was developed. This model allows a given soil to be described with only one set of parameters, for example from a loose to a dense state or from a normally consolidated to an over-consolidated state. This feature is useful for taking into account initial states or for observing a change in the main behaviour due to a large change in the confining loading conditions.